Co-construire une méthode de prélèvement de surface pour les médicaments anticancéreux : vers de nouveaux apprentissages pour la prévention des expositions à des produits chimiques - Valentin Lamarque; Adélaïde Nascimento; Leïla Boudra; Guillaume Swierczynski; Alain Garrigou (Activités)
Despite the efforts made in risk prevention to use anti-cancer drugs (AD) to reduce the internal contamination of professionals exposed to chemotherapy, recent studies show that this problem remains relevant. In this regard, in its report published in 2021, the French Agency for Food, Environmental and Occupational Health and Safety (agence nationale de sécurité sanitaire de l’alimentation, de l’environnement et du travail (ANSES)) points out that exposure to ADs is an enigma that needs to be characterized, where evaluation must be intensified, and where healthcare workers lack knowledge and training. In the face of mostly top-down prevention methods that are no longer sufficient, we therefore believe that the methods must be learning methods, i.e. they should encourage learning in and through work to support the development and transformation of the work of professionals, by the professionals themselves. To this end, this article proposes a hybrid method between ergotoxicology and expansive learning theory, based on the first stage of an ongoing formative research-intervention. Using the principle of double stimulation, we will help healthcare workers to develop knowledge about exposure, based on their own experiences, which will prove helpful when working with them to select the sampling surfaces to be used. The links made between exposure, actions, protection, and the possibility of contamination, will then allow healthcare workers to construct intermediate objects useful for continuing the intervention and supporting learning at a collective level.